THE ALARINJO THEATRE: (THE STUDY OF A YORUBA THEATRICAL ART FROM ITS EARLIEST BEGINNINGS TO THE PRESENT-TIMES) (1969)
This study describes the art and development of the Alarinjo Theatre from its earliest beginnings to the present times. The origin and development of the theatre are traced to the descendants of the Oba, believed to be the autochthones of Yoruba- land and worshippers of Obatala, the Yoruba supreme divinity. By giving material existence to Obatala, they displayed an instinct for impersonation and ritualistic expression which leads to developmental drama. As a natural reaction to the deprivation which they suffered at the hands of their enemies (a party of immigrants), they had recourse to stratagems by which invariably, they developed the means of drama; namely, religion, art and disguise. The ‘masquerade’ was first used by the Igbo' followers of Obatala to terrorise and plunder the Ife city-state out of which they had been driven by a party of immigrants believed to have been led by Oduduwa. At a later period, the Nupe (supposedly under the influence of the descendants of the Oba who had sojourned in that country after the dispersal from Ife) used the 'masquerade' to prevail upon the Yoruba of Oyo. The Yoruba who at that time worshipped the ‘masquerade’ as ancestral spirit had believed that the Nupe soldier-masquerades were ancestors who had re-appeared on the side of their enemy. They therefore abandoned the Oyo city-state and went into exile. In a rapprochement that followed during the reign of Ofinran (c. 1544), it became clear that the descendants of Oba who had returned to the fold from the Nupe country, had knowledge of the secret of the 'masquerade'. The Egungun Society was formed as a conjoint association of two clans - the Oba (Yoruba indigenes) and the Igbori (Tapa extraction). With this association, both the worship of the ancestor as egungun (masquerade) and the use of the egungun for social action were brought together under a hierarchy. The theatre emerged from three developmental phases - ritual, festival and theatre. The process shows the treatment and use of the egungun for both ritual and secular occasions. It was Ologbin Ologbojo, a descendant of the Oba, who adopted the 'masquerade' for the purpose of furthering his duty as retainer and head of court-entertainers. With these court-masques, therefore, the third and final phase in the development of the theatre from religious dramatic roots was reached. By about the second half of the sixteenth century, the theatre had been born. The theatre flourished extensively during the eighteenth century but mostly within Court circles and participated in the annual egungun festivals. With Esa Ogbin (who adopted the title 'Ologbojo' for his professional role) leading a band of costumed-players, the theatre extended its operations outside of the Court and throughout the Oyo empire. Other professional masque-drama-turgs followed in his footsteps. The fall of the empire during the early part of the nineteenth century did not adversely affect the fortunes of the theatre; on the contrary, it contributed to its artistic development and professional growth. The troupes travelled far beyond the Oyo areas and into the new Ibadan sphere of influence where they became - popularly known as the 'AlArlnjd'. Towards the end of the century and thenceforward, however, the corroding influence of Islam and Christianity on the structure of the Yoruba society questioned the continued existence of the theatre. The form and style of the theatre arise from the generalised concept of Yoruba art, namely, that the artist proceeds by induction rather than by deduction. Although the artist, normally, operates within a transcendental frame of mind that inspires him to accomplish his objective, the results of his work seem superficial to the casual observer. The substance of what the masque-drama turg wishes to communicate or share with his audience is revealed in the material of his creation which also underlines his main pre-occupations, namely, religion and human situations. Thus, in the theatrical 'repertoire', there are two types of masques - the spectacles and the revues. While the former are designed to meet religious objectives, the latter are sketched out as comments on happenings in the society. Although the spectacles are serious drama in intent, yet they are sometimes given satirical turns; but the revues are always comical. The root-elements of the theatre are the mask, the chant, and the dance; but a performance is the sum total of all of these and the unified product of gesture and costume. The theatre has specific obligations to the audience with idiom it communicates. Its functions over and above divertissement include education and edification. Bat the art of the theatre can be better appreciated only within the framework of Yoruba aesthetics and the sensibilities of the people. During the height of its influence, the theatre provided s gainful employment for many people outside the original lineage that first developed the art. As time went on, however, it could not escape being affected by the forces of change which had been at work in the Yoruba society from about the middle of the nineteenth century. With the introductions into the Yoruba society of other forms of entertainment based on European models towards the end of the nineteenth century, the Alarinjo Theatre faced a gloomy prospect. Traces of its influence have been found in the 'new theatres'. While it yet thrives by appealing to the taste of the uneducated masses, its means have failed to attract the rising generation of western-educated and acculturated people who patronise the 'new theatres'. With the increasing popularity of the 'new theatres' therefore, the Alarinjo Theatre is bound to fade out of existence. It will, however, leave behind its own undying influence on the new forms.